Brain tissue oxidative damage as a possible mechanism for the deleterious effect of a chronic high dose of estradiol on learning and memory in ovariectomized rats Dano oxidativo ao tecido cerebral como possível mecanismo de efeito deletério da alta dose crônica de estradiol no aprendizado e memória de ratas ooforectomizadas - Fatimeh Khodabandehloo; Mahmoud Hosseini; Ziba Rajaei; Mohammad Soukhtanloo; Esmaeil Farrokhi; Mohsen Rezaeipour (Arquivos de Neuro-Psiquiatria)
In addition to antioxidative effects, estrogens also exert pro-oxidative actions. The effect of chronic administration of a high dose of estradiol valerate on Morris water maze tasks and brain tissues oxidative damage was investigated. The Sham-Est and OVX-Est groups were treated with estradiol valerate (4 mg/kg) for 12 weeks. Escape latency and traveled path in the Sham-Est and OVX-Est groups were significantly higher than in the Sham and OVX groups (p≪0.01 and p≪0.001). In the probe trial, the animals of the Sham-Est and OVX-Est groups spent lower time in Q1 compared to Sham and OVX groups (p≪0.05 and p≪0.001). In Sham-Est and OVX-Est groups, the brain tissue total thiol concentration was significantly lower, and malondialdehyde (MDA) concentrations were higher than in the Sham and OVX groups (p≪0.05 and p≪0.001). It is concluded that administration of high exogenous levels of estradiol impairs performance and enhances oxidative stress. Além dos efeitos antioxidantes, os estrógenos também têm ação pró-oxidativa. Foi investigado o efeito da administração crônica de alta dose de valereato de estradiol no desempenho do labirinto aquático de Morris e o dano oxidativo ao tecido cerebral. Os grupos Sham-Est e OVX-Est foram tratados com valereato de estradiol (4 mg/kg) por 12 semanas. O tempo de latência para escapada e o caminho percorrido foram significativamente maiores nos grupos Sham-Est e OVX-Est em relação aos grupos Sham e OVX (p≪0,01 e p≪0,001). No estudo probe, os animais dos grupos Sham-Est e OVX-Est levaram menos tempo no Q1 em comparação aos grupos Sham e OVX (p≪0,05 e p≪0,001). Nos grupos Sham-Est e OVX-Est, a concentração total de tiol foi significativamente menor, enquanto a concentração de malondialdehydo (MDA) for maior do que aquela dos grupos Sham e OVX (p≪0,05 e p≪0,001). Concluiu-se que a administração de altas doses de estradiol exógeno compromete o desempenho e aumenta o estresse oxidativo naqueles animais.